Psychophysics in a Web browser? Comparing response times collected with JavaScript and Psychophysics Toolbox in a visual search task - de Leeuw, Joshua R.; Motz, Benjamin A. (Behavior research methods, 2016)
Behavioral researchers are increasingly using Web-based software such as JavaScript to conduct response time experiments. Although there has been some research on the accuracy and reliability of response time measurements collected using JavaScript, it remains unclear how well this method performs relative to standard laboratory software in psychologically relevant experimental manipulations. Here we present results from a visual search experiment in which we measured response time distributions with both Psychophysics Toolbox (PTB) and JavaScript. We developed a methodology that allowed us to simultaneously run the visual search experiment with both systems, interleaving trials between two independent computers, thus minimizing the effects of factors other than the experimental software. The response times measured by JavaScript were approximately 25 ms longer than those measured by PTB. However, we found no reliable difference in the variability of the distributions related to the software, and both software packages were equally sensitive to changes in the response times as a result of the experimental manipulations. We concluded that JavaScript is a suitable tool for measuring response times in behavioral research.